The Paris Agreement and the inherent inconsistency of climate policymaking. (7th September 2016) - Geden, Oliver
Abstract : Since the adoption of the Paris Agreement, the actual meaning of many crucial aspects of that agreement still remains fairly unclear. This has lead to extensive framing efforts, for example on the 5‐year review mechanism. What has been largely overlooked, however, are the decisions on quantified climate stabilization targets. Until now, there has been no serious questioning of the intention to limit the temperature increase to 2 or even 1.5 °C. Not that many in the climate research community seem to grasp the political rationalities behind the setting of long‐term policy targets. Even the mainstream policy discourse assumes consistency between talk, decisions, and actions. Accordingly, a decision on a certain climate target is presented and perceived as an act of deliberate choice, that will be followed up with the deployment of appropriate measures. In real‐world policymaking, however, many decisions are viewed as independent organizational products, not necessarily requiring appropriate action. Despite the cultural norm of consistency, inconsistency is an inherent and inevitable feature of policymaking. This is particularly problematic in public domains with a deliberately transformative agenda like climate policy, which is characterized by long‐term planning and a high demand for scientific advice. But if consistency of talk, decisions, and actions cannot be assumed, then concepts like evidence‐based policymaking become essentially devoid of meaning. Simply delivering the best available knowledge to policymakers might even have counterintuitive effects. In the future, policy‐driven climate researchers and advisors must critically assess how their work is actually being interpreted and used in policymaking processes. WIREs Clim Change 2016, 7:790–797. doi: 10.1002/wcc.427 This article is categorized under: Policy and Governance > International Policy Framework